Parameters of performance: A deep dive into liquid-to-air CDU assessment - Ali Heydari; Ahmad R. Gharaibeh; Mohammad Tradat; Qusai Soud; Yaman Manaserh; Vahideh Radmard; Bahareh Eslami; Jeremy Rodriguez; Bahgat Sammakia (Case Studies in Thermal Engineering, 2024)
The rapid growth in data center workloads and the increasing complexity of modern applications have led to significant contradictions between computational performance and thermal management. Traditional air-cooling systems, while widely adopted, are reaching their limits in handling the rising thermal footprints and higher rack power densities of next-generation servers, often resulting in thermal throttling and decreased efficiency, emphasizing the need for more efficient cooling solutions. Direct-to-chip liquid cooling with cold plates has emerged as a promising solution, providing efficient heat dissipation for high-performance servers. However, challenges remain, such as ensuring system stability under varying thermal loads and optimizing integration with existing infrastructure. This comprehensive study digs into the area of data center liquid cooling, providing a novel, comprehensive experimental investigation of the critical steps and tests necessary for commissioning coolant distribution units (CDUs) in direct-to-chip liquid-cooled data centers. It carefully investigates the hydraulic, thermal, and energy aspects, establishing the groundwork for Liquid-to-Air (L2A) CDU data centers. A CDU's performance was evaluated under different conditions. First, the CDU's maximum cooling capacity was evaluated and found to be as high as 89.9 kW at an approach temperature difference (ATD) of 18.3 °C with a 0.83 heat exchanger effectiveness. Then, to assess the cooling performance and stability of the CDU, a low-power test and a transient thermohydraulic test were conducted. The results showed instability in the supply fluid temperature (SFT) caused by the oscillation in fan speed at low thermal loads. Despite this, heat removal rates remained constant across varying supply air temperatures (SATs), and a partial power usage effectiveness (PPUE) of 1.042 was achieved at 100 % heat load (86 kW) under different SATs. This research sets a foundation for improving L2A CDU performance and offers practical insights for overcoming current cooling limitations in data centers.